Operations management strategy of selecting business location using AHP / Mohd Sahar Sauian - Sauian, Mohd Sahar (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2006)
The choice of location is of paramount importance in modern business decision. It has become one of the most important operational strategies in managing operations of large business organizations. The three common approaches of location selections are Factor-Rating Method, the Centre of Gravity Approach and the Transportation Model approach. While these approaches are common to the practitioners of operations management, there may be other quantitative tools that can be adopted in deciding location strategies. This paper attempts to highlight the use of Analytic Hierarchy Process (AHP) approach in selecting business location.